Football Supporter Activism as a Political Force in Modern Football Governance and Reform - Paul Moento; Marolahy Jacquot Urbain; Ari Wirachandra; Yuni Indah (Unnes Political Science Journal, 2026)
Football is no longer merely a form of sport and entertainment but has developed into a social arena in which political, cultural, and collective identities interact. This study analyzes the development of football supporter activism as a new form of sociopolitical participation and examines its implications for digital mobilization, club policies, and modern football governance. A qualitative approach was employed through a literature review of scholarly articles, research reports, and other relevant sources. The findings show that supporters have shifted from passive consumers to collective actors with significant social and political influence. Their activism addresses not only club-related interests but also social justice, inclusivity, human rights, and resistance to the excessive commercialization of football. Social media strengthens connective action by enabling rapid coordination across geographical boundaries and integrating online and offline activism. Supporter pressure also encourages clubs to adopt more inclusive, transparent, welfare-oriented, and socially responsible policies. In governance, supporters are increasingly recognized as stakeholders who promote accountability, regulatory reform, and more democratic ownership models. However, excessive commercialization, financial inequality, intergroup conflict, and inadequate digital regulation remain significant challenges. The study advances understanding of supporter activism and calls for adaptive, inclusive, and sustainable football policies.